Digital Logic and Computer Design - Mano, M. Morris (Englewood Cliffs, N. J. Prentice-Hall, 1979)
This book presents the basic concepts used in the design and analysis of digital systems and introduces the principles of digital computer organization and design.
Include Index
Keywords: Digital integrated circuits -- Logic design -- Electronic digital computers -- Logic circuits